Pentingnya Pendidikan Karakter pada Generasi Milenial di Era Digital - Aulia Arma Putri; Maya Nurantika; Siti Tiara Maulia (Departement of Mathematics Education, 2023)
Character education itself was previously only imposed on two subjects, namely religious subjects and PKN, especially those related to the morals and character of students. Character education is the cultivation and development of positive character values ​​for students so that students have a good personality in accordance with the norms that apply in schools and in society. Implementation of character education in schools, habituation of students to good behavior needs to be supported by the example of teachers and principals (principals), along with all the elements that exist in the school. The research method used in this study is a literature review or literature study. Which contains the theories used related to the problems in this study. As for this research, the formulation of the problem is to find out